Pronounced muscle deoxygenation during supramaximal exercise under simulated hypoxia in sprint athletes - Oguri, K.; Fujimoto, H.; Sugimori, H.; Miyamoto, K.; Tachi, T.; Nagasaki, S.; Kato, Y.; Matsuoka, T. (Journal of Sports Science & Medicine, 2008)
The purpose of this study was to determine whether acute hypoxia alters the deoxygenation level in vastus lateralis muscle during a 30 s Wingate test, and to compare the muscle deoxygenation level between sprint athletes and untrained men. Nine male track sprinters (athletic group, VO2max 62.5 ± 4.1 ml/kg/min) and 9 healthy untrained men (untrained group, VO2max 49.9 ± 5.2 ml·kg-1·min-1) performed a 30 s Wingate test under simulated hypoxic (FIO2 = 0.164 and PIO2 = 114 mmHg) and normoxic conditions. During the exercise, changes in oxygenated hemoglobin (OxyHb) in the vastus lateralis were measured using near infrared continuous wave spectroscopy. Decline in OxyHb, that is muscle deoxygenation, was expressed as percent change from baseline. Percutaneous arterial oxygen saturation (SpO2), oxygen uptake (VO2), and ventilation (VE) were measured continuously. In both groups, there was significantly greater muscle deoxygenation, lower SpO2, lower peakVO2, and higher peakVE during supramaximal exercise under hypoxia than under normoxia, but no differences in peak and mean power output during the exercise. Under hypoxia, the athletic group experienced significantly greater muscle deoxygenation, lower SpO2, greater decrement in peakVO2 and increment in peakVE during the exercise than the untrained group. When the athletic and untrained groups were pooled, the increment of muscle deoxygenation was strongly correlated with lowest SpO2 in the 30 s Wingate test under hypoxia. These results suggest that acute exposure to hypoxia causes a greater degree of peripheral muscle deoxygenation during supramaximal exercise, especially in sprint athletes, and this physiological response would be explained mainly by lower arterial oxygen saturation.